High‐Frequency Oscillation Networks and Surgical Outcome in Adult Focal Epilepsy. Issue 4 (18th March 2019) - González Otárula, Karina A.; von Ellenrieder, Nicolás; Cuello‐Oderiz, Carolina; Dubeau, François; Gotman, Jean
Abstract : Objective: To investigate whether high‐frequency oscillations (HFOs) show spatiotemporal propagation and assess the relevance of the earliest oscillations in relation to the seizure onset zone (SOZ) and postsurgical outcome. Methods: We retrospectively investigated the intracerebral electroencephalography (EEG) of patients who became seizure free after subsequent surgery. We marked HFOs during 1 hour of recordings. We calculated the time delay between pairs of channels as the median delay between their HFOs and constructed a time line of the delay of each channel with respect to the earliest channel (first source channel). A network was defined when a temporal order could be established among the channels based on the existence of statistically significant delays. Results: Fifteen patients with good surgical outcome were included. We found ripple networks in all patients, and fast ripple networks in 9. For ripples, first source channels were found in a higher proportion in the SOZ than the rest of the network channels (15 of 27 [56%] versus 93 of 262 [35%]; p  = 0.04). For both ripples and fast ripples, first source channels were resected more often that the rest of the network channels (ripples: 13 of 27 [48%] versus 65 of 262 [25%]; p  = 0.01; fast ripples: 8 of 9 [89%] versus 17 of 40 [43%]; p  = 0.002); channels with the highest rates of ripples and fast ripples were resected in a similar proportion. Interpretation: These results demonstrate that interictal HFOs are organized in networks and indicate a possible need for the resection of first source channels. However, resecting them is not superior to resecting channels with highest rates of HFOs. Ann Neurol 2019;85:485–494